Potential of Selected Mangrove Streptomyces as Plant Growth Promoter and Rice Bakanae Disease Control Agent - Wasu Pathom-aree (Science Faculty of Chiang Mai University, 2019)
Rice is global staple food consumed worldwide. Thai jasmine rice (Oryza sativa KDML 105) is Thailand most important economic crop. However, the prevalence of Bakanae diseases from fungal pathogen Fusarium fujikuroi is the major problem for rice cultivation in Thailand. The disease affects both quantity and quality of rice resulting in the decreasing of rice yield. Large volume of harmful chemical substances is being used to control the outburst of Bakanae disease. In this study, two selected mangrove Streptomyces were tested for their plant growth promoting activities and growth inhibiting activity on F. fujikuroi. In vitro experiments indicated that, isolate S2-SC16 is the most effective to inhibit the germination of F. fujikuroi CMU-F02 conidia. In vivo experiment also demonstrated an ability of Streptomyces isolate S2-SC16 to control F. fujikuroi CMU-F02 infection in rice seeds as the seed infected percentage is reduced from 23% to 6%. Furthermore, in pot experiment, isolate S2-SC16 not only shows an ability to restrict the infection of F. fujikuroi CMU-F02, but also shows an ability to promote the growth of rice seedlings by increasing numbers of growth parameters including root length, shoot height, leaf width and weight. Phylogenetic analysis based on 16S rRNA gene sequence indicated that isolate S2-SC16 is closely related to Streptomyces iranensis HM 35T (99.55% similarity). From the results of our study, there is the possibility of using mangrove actinomycetes as plant growth promoting and alternative environmental friendly control agents for Bakanae disease in Thai jasmine rice KDML 105. S. iranensis isolate S2-SC16 is a candidate for the development as plant supplement and biocontrol agent.